Delayed Facial Nerve Paralysis after Vestibular Schwannoma Resection - Yawn, Robert J.; Dedmon, Matthew M.; Xie, Deborah; Thompson, Reid C.; O'Malley, Matthew R.; Bennett, Marc L.; Rivas, Alejandro; Haynes, David S. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective To describe the incidence and clinical course of patients who develop delayed facial nerve paralysis (DFNP) after surgical resection of vestibular schwannoma.Setting Tertiary skull base center.Methods Retrospective chart review.Results Two hundred and forty six consecutive patients, who underwent surgical resection for vestibular schwannoma at a single center between 2010 and 2015, were analyzed. Of these patients, 22 (8.9%) developed DFNP, defined here as deterioration of function by at least 2 House–Brackmann (HB) grades within 30 days in patients with immediate postoperative HB ≤ 3. The mean age of DFNP patients was 47.2 years (range: 17–67) and 16 (73%) were female. The mean tumor size in greatest dimension was 2.1 cm (range: 0.7–3.5 cm). At the conclusion of each case, the facial nerve stimulated at the brainstem. Mean immediate postoperative facial nerve function was HB 1.8 (range: 1–3). Average facial nerve function at the 3-week-postoperative visit was 4.4 (range: 2–6). In 1-year, 8 patients (36%) recovered HB 1 function, 10 patients (46%) recovered to HB 2, and 2 patients (9%) were HB 3. The remaining 2 patients did not recover function and were HB 6 at last follow-up. Initial postoperative facial nerve function (HB 1 or HB 2) was associated with improved recovery to normal (HB 1) function (p = 0.018).Conclusion A majority of patients that develop delayed paralysis will recover excellent facial nerve function. Patients should be counseled; however, a small percentage of patients will not recover function long-term, despite having a previously functioning and anatomically intact nerve.
Keywords: vestibular schwannoma; acoustic neuroma; facial paralysis; skull base surgery; translabyrinthine; suboccipital; retrosigmoid; delayed facial paralysis